Hydogeochemical assessment of surface water and ground water quality in Agbowo-Orogun area of Ibadan, southwestern Nigeria (2007)
"The Agbowo-Orogun area of Ibadan, which is within the basement complex of southwestern Nigeria, is underlained by banded gneiss of the migmatites-gneiss complex. A total of thirty-five water sample, made up of thirty-two from groundwater and three from surface water, were analyzed for their physico-chemical characteristics with the aim of assessing their quality and usability. Results of some physico-chemical parameters show average values of 8.61 pH; 749 49ps/cm EC; 218 50 mg/l TDS; 84.40 turbidity; 323.14 pt/co unit colour; 54.94 mg/l Na‘; 49.75mg/l Ca2*; 28.24mg/l Mg , 23 54 mg/l K*. 1 05 mg/l Fe* 229 14 mg/l HCO; 128.23 mg/l Cl'; 14 86mg/l NO3; 7.30mg/l SO<2; 4 60 mg/l PO<3 and 1 31 mg/l F Average values of total hardness (TH) and sodium absorption ratio are 230 68 mg/l and 1 95 respectively. The relative abundance of cations is in the order of Na*>Ca2*>Mg2*>K*>Fe2* while those of anions are; HC03'>Cr>N0j'>S0«2'>P042 --F R-mode factor analysis shows five factor loadings and bi-log plots of TDS versus Na*/ (Na* ♦ Ca2*) all indicate that the bulk of the chemistry of the water is modified by weathering of the associated rocks. Six water groups were identified, based on characterization using the pipor bilinear diagram These include; Ca- (Mg)-Na- HCO3, Ca-(Mg)-Na-CI-(SO<)-HC03, Ca-(Mg)-HC03, Ca-Mg-(S04>-HC03, Ca-(Mg)-SC>4 and Na-(K)-HC03 thus reflecting diverse effects of bedrock lithologies, base exchange processes, precipitation and weathering Both water sources are in general, slightly alkaline with low to medium sodium hazards The pH, Ca2* and SO42' are within tns permissible limits of WHO standard for both water sources. Concentrations of Na*, NO3 Cl', HCO3 conductivity and TDS are higher than maximum permissible limits for the surface water and may be attributed to anthropogenic effects However it can be observed that both the groundwater and surface water sources are suitable for agricultural purposes while the groundwater in particular, is acceptable for domestic uses. "